More than just green: The role of bottom-up initiatives for socially just urban green development - Heeg,Paulina Maria (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
In response to growing social injustices in cities, bottom-up initiatives are increasingly recognised as sites of resistance and experimentation. I examine how the PARKS project in Hamburg, a temporary, collectively governed green space, challenges neoliberal urban development and envisions socially just green spaces. Adopting a case study approach, I draw on semi-structured interviews, participant observation, and document analysis. Theoretically, my research is grounded in urban environmental justice, the right to the city, and urban commons literature. The analysis shows how such initiatives create actually existing commons through practices of care, participation, shared governance and advances justice by addressing barriers faced by disadvantaged groups. Yet, it reveals limitations, including risks of co-optation through green branding which, without complementary anti-displacement measures, can fuel green gentrification, as well as risks of domestication via institutionalisation, lack of ownership and barriers to participation. These findings illustrate deep-seated tensions between bottom-up engagement and broader urbanisation dynamics.
Keywords: bottom-up initiatives; urban greening; environmental justice; urban commons; right to the city; Hamburg; sustainability science